Factors associated with preventable infant mortality in 2020: a Brazilian population-based study - Sousa, Mikaelly Rayanne Moraes [UNESP]; Parada, Cristina Maria Garcia de Lima [UNESP]; Nunes, Hélio Rubens de Carvalho [UNESP] (FapUNIFESP (SciELO), 2024)
Objectives: to identify factors associated with preventable infant deaths, classified as neonatal and post-neonatal. Methods: this is an epidemiological and population-based study relating to 2020. Data from the Mortality Information System (MIS) and the preventability classification proposed in the Brazilian Health System List of Causes of Deaths Preventable by Interventions were used. Results: prematurity, living in the North and Northeast regions and the occurrence of the event at home were associated with preventable neonatal deaths. To the avoidable post-neonatal component, death outside the hospital, low maternal education and children of brown or yellow color/race were associated. Conclusions: the main risk factor associated with preventable deaths was prematurity, in the case of neonatal death. Low maternal education and occurrence outside the hospital were associated with post-neonatal deaths.
Factores asociados a la mortalidad infantil evitable en 2020: estudio poblacional brasileño
Fatores associados à mortalidade infantil evitável no ano de 2020: estudo brasileiro de base populacional
Keywords: Epidemiological Studies; Health Care Quality; Health Information Systems; Infant Mortality; Vital Statistics